Empress vs. Spider-Man: Margaret Cavendish on pure and applied mathematics - Peterman, Alison (Synthese (Dordrecht), 2019)
The empress of Margaret Cavendish's The Blazing World dismisses pure mathematicians as a waste of her time, and declares of the applied mathematicians that "there [is] neither Truth nor Justice in their Profession". In Cavendish's theoretical work, she defends the Empress' judgments. In this paper, I discuss Cavendish's arguments against pure and applied mathematics. In Sect. 3, I develop an interpretation of some relevant parts of Cavendish's metaphysics and epistemology, focusing on her anti-abstractionism and what I call her 'assimilation' view of knowledge. In Sects. 4 and 5, I use this to develop Cavendish's critiques of pure and applied mathematics, respectively. These critiques center on the claims that mathematics purports to describe non-beings, that nature is infinitely and irreducibly complex, and, perhaps most originally, that mathematical thinking (like other formal methods in philosophy) deforms the subject of representation, not just the object.